Hospital admissions and surgical treatment of children with lower-limb deficiency in Finland. (December 2019) - Syvänen, J.; Helenius, I.; Koskimies-Virta, E.; Ritvanen, A.; Hurme, S.; Nietosvaara, Y.
Background and Aims: There are no population-based studies about hospital admissions and need for surgical treatment of congenital lower-limb deficiencies. The aim is to assess the impact children with lower-limb deficiencies pose to national hospital level health-care system. Materials and Methods: A population-based study was conducted using the national Register of Congenital Malformations and Care Register for Health Care. All 185 live births with lower-limb deficiency (1993–2008) were included. Data on hospital care were collected until 31 December 2009 and compared to data on the whole pediatric population (0.9 million) live born in 1993−2008. Results: The whole pediatric population had annually on average 0.10 hospital admissions and the mean length of in-patient care of 0.3 days per child. The respective figures were 1.5 and 5.6 in terminal lower-limb amputations (n = 7), 1.1 and 3.9 in long-bone deficiencies (n = 53), 0.6 and 1.9 in foot deficiencies (n = 26) and 0.4 and 2.6 in toe deficiencies (n = 101). Orthopedic surgery was performed in 72% (5/7) of patients with terminal amputations, in 62% (33/53) of patients with long bone, in 58% (14/24) of patients with foot and in 25% (25/101) of patients in toe deficiencies. Half (54%) of all procedures were orthopedic operations. Conclusion: In congenital lower-limb deficiencies the need of hospital care and the number of orthopedic procedures is multiple-fold compared to whole pediatric population. The burden to the patient and to the families is markedly increased, especially in children with terminal amputations and long-bone deficiencies of lower limbs.